PERMANENT CENTRAL DIABETES INSIPIDUS IN A POST TRANSSPHENOIDAL SURGERY PATIENT: A CASE REPORT - Efendi, Yanne Pradwi; Kam, Alexander; Aprilia, Dinda; Decroli, Eva; Syahbuddin, Syafril (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Diabetes insipidus (DI) is a disorder characterized by the excretion of large volumes of hypotonic urine. Four types of DI must be differentiated: central DI (cDI), nephrogenic DI (nDI), gestational DI, and primary polydipsia. Central DI can be transient, particularly as a complication of pituitary surgery. Permanent central DI is a rare complication of pituitary surgery. CASE A 48-year-old female was referred from the neurosurgery department with a nine-month history of polyuria (urination exceeding 3 liters daily), polydipsia (excessive thirst), fatigue, constipation, and cold intolerance. Nine months prior, she underwent transsphenoidal surgery for a pituitary macroadenoma. She reported no prior history of hormonal abnormalities or use of antithyroid medication. Her body mass index (BMI) was 24.5 kg/m², and her thyroid gland was not enlarged. Laboratory results showed: TSH 0.25 mIU/mL, FT4 9.5 pmol/L, cortisol 312 µg/dL, prolactin 268 ng/mL, LH 2 mIU/mL, FSH 11.35 mIU/mL, estradiol 62.3 pg/mL, sodium 143 mmol/L, urine osmolality 100 mOsm/kg, serum osmolality 292 mOsm/kg. A water deprivation test (WDT) revealed a urine osmolality of 212 mOsm/kg, which increased to 499 mOsm/kg after desmopressin administration. The diagnoses were central diabetes insipidus (cDI) (post-operative, permanent), central hypothyroidism, and hypogonadotropic hypogonadism. Treatment consisted of desmopressin 0.6 mg once daily and thyroxine 50 mcg once daily. After six months, her signs and symptoms improved. CONCLUSION Permanent central DI occurs when the hypothalamus and/or pituitary stalk is irreversibly injured. It is important to monitor DI in post-pituitary surgery. One of the diagnostic tests used is WDT.